2015
DOI: 10.4103/0300-1652.169744
|View full text |Cite
|
Sign up to set email alerts
|

Malaria rapid diagnostic test in children: The Zamfara, Nigeria experience

Abstract: Background:Malaria remains a major cause of under-five morbidity and mortality in Nigeria, and prompt diagnosis occupies a strategic position in its management. Malaria rapid diagnostic test (RDT), a nontechnical, easy to perform test promises to meet this need. It is important to locally document the usefulness of the use of RDT in making prompt malaria diagnosis in children.Objective:To determine the prevalence of malaria and evaluate the diagnostic performance of malaria RDT kit in febrile under-five childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
16
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 9 publications
8
16
6
Order By: Relevance
“…The present study reports a transmission rate of about 40% in symptomatic and healthy individuals in which the latter contributes more than half (26%) of the total infection. Malaria prevalence in this study was significantly higher than rates reported in hospital population from some southwest region [14][15] but similar to rates reported in other southwest and Northern Nigeria [16,[21][22][23]. The reasons for this are not farfetched, our study evaluated both healthy and hospital population thus revealing the intensities of malaria transmission in a general population.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The present study reports a transmission rate of about 40% in symptomatic and healthy individuals in which the latter contributes more than half (26%) of the total infection. Malaria prevalence in this study was significantly higher than rates reported in hospital population from some southwest region [14][15] but similar to rates reported in other southwest and Northern Nigeria [16,[21][22][23]. The reasons for this are not farfetched, our study evaluated both healthy and hospital population thus revealing the intensities of malaria transmission in a general population.…”
Section: Discussionsupporting
confidence: 83%
“…Studies have reported variable HRP-2 RDT tests based on age and infection rates, post-treatment persistence of parasite antigens, level of immunity and in different endemic settings [10,11]. RDTs generally diagnose P. falciparum malaria with a sensitivity of >90% [8,[12][13][14][15][16], an advantage in endemic areas will be detection of asymptomatic parasitemia. Hence, HRP-2 RDTs could serve as a tool for mapping intensities of transmission in untreated population, because HRP-2 protein can be detected both in asexual parasites and from young gametocytes of P. falciparum.…”
Section: Introductionmentioning
confidence: 99%
“…The use of RDT in hospitals would also decrease turn-around time providing physicians with feedback and results in a timely manner. Overtreatment of children was also reported in Samara hospital, Nigeria where 57% of febrile children admitted to the hospital received antimalarial medication for treatment of presumed malaria before the presentation [ 87 ]. When evaluating the sensitivity and specificity of RDT for diagnosis of pediatric malaria, the authors found that RDT had a sensitivity of 40.3% and a specificity of 89.6%.…”
Section: Rapid Diagnostic Testsmentioning
confidence: 99%
“…In Kenya, World Health Organization Integrated Management of Childhood Illness (IMCI), danger signs (unable to drink/ breastfeed, vomits everything, convulsions, lethargic/unconscious) and fever lasting ≥7 days and ≥39° C were predictors for prescribing antimalarial drugs [15]. In Nigeria, fever, decreased appetite, and temperatures between 38°C and 41°C were associated with children prescribed with antimalarial drugs [16]. In Tanzania, health care providers working at hospitals significantly increased odds about four-fold to prescribe antimalarial as compared to health care providers working in the dispensaries[9].…”
Section: Introductionmentioning
confidence: 99%